ChemInform Abstract: Marine Protein Hydrolysates: Their Present and Future Perspectives in Food Chemistry — A Review. Issue 26 (June 2015) - Vijaykrishnaraj, M.; Prabhasankar, P.
Abstract Review: 114 refs.